2019
DOI: 10.1161/circheartfailure.119.005819
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pulmonary Hypertension With Angiotensin II Receptor Blocker and Neprilysin Inhibitor Sacubitril/Valsartan

Abstract: Background: Angiotensin II has been implicated in maladaptive right ventricular (RV) hypertrophy and fibrosis associated with pulmonary hypertension (PH). Natriuretic peptides decrease RV afterload by promoting pulmonary vasodilation and inhibiting vascular remodeling but are degraded by neprilysin. We hypothesized that angiotensin receptor blocker and neprilysin inhibitor, sacubitril/valsartan (Sac/Val, LCZ696), will attenuate PH and improve RV function by targeting both pulmonary vascular and RV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 15 publications
0
60
0
1
Order By: Relevance
“…ACE-I and ARB are cornerstone not only for hypertension but also for HF treatment. An emerging topic of interest is the potential role of angiotensin receptor-neprilysin inhibitor (ARNI) sacubitril/ valsartan in patients with pulmonary vascular remodeling, pulmonary hypertension, and right ventricular overload related to lung diseases (10). The synergistic effects of RAS and neprilysin inhibition, versus RAS inhibition alone, may magnify the protective benefits of natriuretic peptides by reducing fibrosis and vascular remodeling and promoting vasodilation and natriuresis (80).…”
Section: Potential Role Of Angiotensin Receptor-neprilysin Inhibitor mentioning
confidence: 99%
See 1 more Smart Citation
“…ACE-I and ARB are cornerstone not only for hypertension but also for HF treatment. An emerging topic of interest is the potential role of angiotensin receptor-neprilysin inhibitor (ARNI) sacubitril/ valsartan in patients with pulmonary vascular remodeling, pulmonary hypertension, and right ventricular overload related to lung diseases (10). The synergistic effects of RAS and neprilysin inhibition, versus RAS inhibition alone, may magnify the protective benefits of natriuretic peptides by reducing fibrosis and vascular remodeling and promoting vasodilation and natriuresis (80).…”
Section: Potential Role Of Angiotensin Receptor-neprilysin Inhibitor mentioning
confidence: 99%
“…The synergistic effects of RAS and neprilysin inhibition, versus RAS inhibition alone, may magnify the protective benefits of natriuretic peptides by reducing fibrosis and vascular remodeling and promoting vasodilation and natriuresis ( 80 ). Given the prevalence and the negative prognostic role of myocardial injury in COVID-19 patients ( 11 ), ARNI may not only be effective in reducing morbidity and mortality in patients with chronic symptomatic HF with reduced ejection fraction (HFrEF) ( 55 ) but may also counterbalance the Ang II-AT 1 R pathway, which has been implicated in maladaptive right ventricular hypertrophy and fibrosis associated with pulmonary hypertension ( 10 ). Indeed, neprilysin inhibition is intimately related to RAS activation, but it is unclear whether ARNI has any impact on ACE2 or in COVID-19 patients.…”
Section: Specific Role Of Ras Pathways In Lung Diseasementioning
confidence: 99%
“…Local tissue-based RAS exacerbates pulmonary hypertension, acute lung injury and experimental lung fibrosis [8]. Thus, blocking of the Angiotensin II receptor type I (AT1R) was associated with reduced SARS-CoV spike protein mediated lung injury [6] and reduced pulmonary hypertension in experimental models [9]. The AT1R blocker valsartan has recently been reported to improve clinical outcomes for patients with chronic obstructive pulmonary disease (COPD) complicated with pulmonary hypertension (DOI:10.1183/13993003.congress-2019.PA2469).…”
mentioning
confidence: 99%
“…It is worth noting that neprilysin inhibition upregulated the ET-1 level, particularly in neprilysin-rich organs like the kidney [21]. However, another study showed that ARNI reduced the plasma ET-1 level in rats with pulmonary hypertension [22]. The various findings may be related to different research subjects and experimental settings.…”
Section: Discussionmentioning
confidence: 97%